2023
DOI: 10.1002/cam4.6575
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lymphangitis carcinomatosis: A peculiar presentation clustering in MET‐amplified gastric cancer

Zhening Zhang,
Yiyi Yu,
Tong Xie
et al.

Abstract: BackgroundThe clinicopathological features of MET‐amplified gastric cancer (GC) and real‐world data on the efficacy of MET‐targeted therapies remain unknown. Pulmonary lymphangitis carcinomatosis (PLC) is a peculiar manifestation of GC, whose management has not been thoroughly described.MethodsThis study analyzed patients diagnosed with MET‐amplified GC or GC with PLC at any time point of the disease course from 2011 to 2021 in two centers. Clinicopathological features and survival outcomes of MET‐amplified GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Patients with MET alterations were more likely to have immune-related AEs compared to patients without MET alterations in a study involving patients receiving PD-1 immunotherapy (100.0% vs. 27.3%; P = 0.09) 29 . A recent in-depth analysis involving patients with MET -amplified gastric cancer in clinical practice and case accumulation showed that patients with MET -amplified gastric cancer have the following clinical characteristics: poorly differentiated tumours 28 ; peritoneal metastases 30 ; and pulmonary lymphangitis carcinomatosis (PLC) 31 . Taken together, these findings suggest that increased attention should focus on identifying gastric cancer patients with MET alterations, especially MET amplification.…”
Section: Met Alterations In Gastric Cancermentioning
confidence: 99%
“…Patients with MET alterations were more likely to have immune-related AEs compared to patients without MET alterations in a study involving patients receiving PD-1 immunotherapy (100.0% vs. 27.3%; P = 0.09) 29 . A recent in-depth analysis involving patients with MET -amplified gastric cancer in clinical practice and case accumulation showed that patients with MET -amplified gastric cancer have the following clinical characteristics: poorly differentiated tumours 28 ; peritoneal metastases 30 ; and pulmonary lymphangitis carcinomatosis (PLC) 31 . Taken together, these findings suggest that increased attention should focus on identifying gastric cancer patients with MET alterations, especially MET amplification.…”
Section: Met Alterations In Gastric Cancermentioning
confidence: 99%